>Hello,
>I get this and don't know how to handle it.
>
> 3
> d 2
>(D11) --- (f(z)) = ------
> 3 2
> dz 1 - z
>(C12) desolve(d11,f(z));
This isn't the most elegant solution but
I got some results by reducing the order
and using ode2 (which only works on 1st and 2nd order DEs).
depends(f3,z)$
u3:ODE2(DIFF(f3,z,1) = 1/(1-z^2),f3,z);
LOG(z + 1) LOG(z - 1)
(D3) f3 = ---------- - ---------- + %C
2 2
The right hand side of u3 can be referenced as rhs(u3).
(can also use rhs(d3) but rhs(f3) doesn't work.)
depends(f2,z)$
u2:ODE2(DIFF(f2,z,1) = rhs(u3),f2,z)$
depends(f1,z)$
u1:ODE2(DIFF(f1,z,1) = rhs(u2),f1,z);
The answer is in u1. Check the results:
diff(rhs(u1),z,3);
ratsimp(%);
1
(D9) - ------
2
z - 1
lp